Retrieval of Large Balloon Fragments During Transcatheter Pulmonary Valve Implantation Using a Novel Retrieval System - Anne C. Taylor, MD; Mohamed Ali H. Ghandour, MD; Asra Khan, MD; Srinath T. Gowda, MD; Flora Nunez-Gallegos, MD; Lynn F. Peng, MD; Jamil A. Aboulhosn, MD; Daniel S. Levi, MD; Doff B. McElhinney, MD; Athar M. Qureshi, MD (JACC: Case Reports, 2023)
The removal of balloon fragments from the pulmonary artery without damaging the pulmonary and tricuspid valves can be difficult. Four cases during transcatheter pulmonary valve replacement are described in which a novel retrieval system was used to facilitate safe removal. (Level of Difficulty: Advanced.)